Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have the following system:

$a b x_0 y - \sqrt{a^2 - x_0^2} (a^2 x - a^2 x_0 + b^2 x_0) = 0$

$ x_0^3 ( a^2-b^2) = a^4 x$

I need to solve it and get $(ax)^{2/3} + (by)^{2/3} = (a^2- b^2) ^{2/3}$

This is the only part I have left on a exercice about computing the evolute of the ellipse using the normal rects (I have to do it that way)

share|cite|improve this question

1 Answer 1

up vote 1 down vote accepted

$x_0(a^2-b^2)=\dfrac{a^4x}{x_0^2}, abx_0y=\sqrt{a^2-x_0^2}(a^2x-x_0(a^2-b^2))=\sqrt{a^2-x_0^2}\left(a^2x-\dfrac{a^4x}{x_0^2}\right) \to $

$(by)^2=(ax)^2\left(\dfrac{a^2}{x_0^2}-1\right)^3 \to (by)^{\frac{2}{3}}=(ax)^{\frac{2}{3}}\left(\dfrac{a^2}{x_0^2}-1\right) \to (ax)^{2/3} + (by)^{2/3}=\dfrac{a^{8/3}x^{2/3}}{x_0^2}=\left(\dfrac{a^8x^2}{x_0^6} \right)^{1/3}=\left(\dfrac{a^4x}{x_0^3} \right)^{2/3}=(a^2-b^2)^{2/3}$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.